Protocol for a randomised trial evaluating the effect of applying gamification to simulation-based endoscopy training. Issue 2 (24th February 2019) - Scaffidi, Michael A; Khan, Rishad; Walsh, Catharine M; Pearl, Matthew; Winger, Kathleen; Kalaichandran, Ruben; Lin, Peter; Grover, Samir C
Abstract : Background: Simulation-based training (SBT) provides a safe environment and effective means to enhance skills development. Simulation-based curricula have been developed for a number of procedures, including gastrointestinal endoscopy. Gamification, which is the application of game-design principles to non-game contexts, is an instructional strategy with potential to enhance learning. No studies have investigated the effects of a comprehensive gamification curriculum on the acquisition of endoscopic skills among novice endoscopists. Methods and analysis: Thirty-six novice endoscopists will be randomised to one of two endoscopy SBT curricula: (1) the Conventional Curriculum Group, in which participants will receive 6 hours of one-on-one simulation training augmented with expert feedback and interlaced with 4 hours of small group teaching on the theory of colonoscopy or (2) the Gamified Curriculum Group, in which participants will receive the same curriculum with integration of the following game-design elements: a leaderboard summarising participants' performance, game narrative, achievement badges and rewards for top performance. In line with a progressive learning approach, simulation training for participants will progress from low to high complexity simulators, starting with a bench-top model and then moving to the EndoVR virtual reality simulator. Performance will be assessed at three points: pretraining, immediately post-training and 4–6 weeks after training. Assessments will take place on the simulator at all three time points and transfer of skills will be assessed during two clinical colonoscopies 4–6 weeks post-training. Mixed factorial ANOVAs will be used to determine if there is a performance difference between the two groups during simulated and clinical assessments. Ethics and dissemination: Ethical approval was obtained at St. Michael's Hospital. Results of this trial will be submitted for presentation at academic meetings and for publication in a peer-reviewed journal. Trial registration number: NCT03176251 .